Analisis Minat Belajar Siswa Smp Terpadu Cokroaminoto dengan Menggunakan Media ICT Berbasis VBA Excel Pada Materi KPK DAN FPB - Wina Nur Alifah Suherman; Susan Amelia; Siti Chotimah (Departement of Mathematics Education, 2019)
This research has a purpose to analyze student interest in learning with the media ICT based VBA excel on theory KPK and FPB which is conducted method using method descriptive qualitative This research was conducted at Cokoaminoto Integrated Middle School in West Bandung Regency with a population of 20 students of class VII. The research instruments provided were Questionnaire interest in learning consists of 20 questions with 5 indicators related to ICT media -based Excel VBA and provided 4 student answer choices namely strongly agree (SS), agree (S), disagree (TS) and strongly disagree (STS. Based on the results of the analysis of the data obtained. namely, with indicators of feeling happy reaching 74.1%, indicators of student interest reaching 74.5%, indicators of student involvement reaching 72.8%, indicators of diligence in learning reaching 66.7%, indicators of perseverance and discipline reaching 73.7%. Then it can be concluded that by using ICT medi a -based Excel VBA can influence student learning interest in ongoing learning.